Development and Validation of RP-HPLC Method for Analysis of Rabeprazole Sodium - Sharna, Sumaya Mahmud; Shuvo, Mehedi Hasan; Ferdaus, Syef; Chowdhury, Sabiha (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Abstract not available Dhaka Univ. J. Pharm. Sci. 18(1): 125-128, 2019 (June)